Muscle and Systemic Molecular Responses to a Single Flywheel Based Iso-Inertial Training Session in Resistance-Trained Men - Annibalini, Giosuè; Contarelli, Serena; Lucertini, Francesco; Guescini, Michele; Maggio, Serena; Ceccaroli, Paola; Gervasi, Marco; Ferri Marini, Carlo; Fardetti, Francesco; Grassi, Eugenio; Stocchi, Vilberto; Barbieri, Elena; et al. (Frontiers in Physiology, 2019)
Growing evidence points to the effectiveness of flywheel (FW) based iso-inertial resistance training in improving physical performance capacities. However, molecular adaptations induced by FW exercises are largely unknown. Eight resistance-trained men performed 5 sets of 10 maximal squats on a FW device. Muscle biopsies (fine needle aspiration technique) and blood samples were collected before (t0), and 2 h (t1) after FW exercise. Blood samples were additionally drawn after 24 h (t2) and 48 h (t3). Paired samples t-tests revealed significant increases, at t1, of mRNA expression of the genes involved in inflammation, in both muscle (MCP-1, TNF-α, IL-6) and peripheral blood mononuclear cells (IkB-α, MCP-1). Circulating extracellular vesicles (EVs) and EV-encapsulated miRNA levels (miR-206, miR-146a) significantly increased at t1 as well. Conversely, muscle mRNA level of genes associated with muscle growth/remodeling (IGF-1Ea, cyclin D1, myogenin) decreased at t1. One-way repeated measure ANOVAs, with Bonferroni corrected post-hoc pairwise comparisons, revealed significant increases in plasma concentrations of IL-6 (t1; t2; t3) and muscle creatine kinase (t1; t2), while IGF-1 significantly increased at t2 only. Our findings show that, even in experienced resistance trained individuals, a single FW training session modifies local and systemic markers involved in late structural remodeling and functional adaptation of skeletal muscle.